Emotional Intelligence as a Strategy for Effective Administration of Schools in a Culturally Pluralist Classroom - Okokoyo, Isabella Ezinwa (NIU Journal of Social Sciences, 2024)
This comprehensive essay explores the integration of emotional intelligence into school administration as a transformative approach with profound implications for culturally pluralist classrooms. It begins by defining emotional intelligence and tracing its historical evolution, addressing debates surrounding its measurement and assessment. The relevance of emotional intelligence in culturally pluralist classrooms is discussed, highlighting the challenges and opportunities of cultural diversity. The pivotal role of emotional intelligence in school administration is analyzed, showcasing how administrators with high emotional intelligence shape school climates, foster student engagement, and enhance academic achievement. Specific emotional intelligence skills and competencies, including self-awareness, self-regulation, empathy, and social skills, are explored in depth. Strategies for developing emotional intelligence in administrators are provided, along with insights into integration into leadership development programs and curricula. Acknowledgment of potential challenges and critiques, along with evidence-based counterarguments, is included. Ongoing debates within academia regarding emotional intelligence in leadership are recognized. The implications of emotional intelligence-based administration for culturally pluralist classrooms are discussed, emphasizing its contribution to inclusive and equitable environments, long-term benefits for students, and broader societal impact. Keywords: Emotional Intelligence, School Administration, Culturally Pluralist Classrooms, Leadership, Diversity, Inclusion